Risk of Aerosol Formation During High-Flow Nasal Cannula Treatment in Critically Ill Subjects. - Bem, Reinout A.; van Mourik, Niels; Klein-Blommert, Rozalinde; Spijkerman, Ingrid JB; Kooij, Stefan; Bonn, Daniel; Vlaar, Alexander P. (Respiratory Care, 2021)
BACKGROUND: There is a persistent concern over the risk of respiratory pathogen transmission, including SARS-CoV-2, via the formation of aerosols (ie, a suspension of microdroplets and residual microparticles after evaporation) generated during high-flow nasal cannula (HFNC) oxygen therapy in critically ill patients. This concern is fueled by limited available studies on this subject. In this study, we tested our hypothesis that HFNC treatment is not associated with increased aerosol formation as compared to conventional oxygen therapy. METHODS: We used laser light scattering and a handheld particle counter to detect and quantify aerosols in healthy subjects and in adults with acute respiratory disease, including COVID-19, during HFNC or conventional oxygen therapy. RESULTS: The use of HFNC was not associated with increased formation of aerosols as compared to conventional oxygen therapy in both healthy subjects (n = 3) and subjects with acute respiratory disease, including COVID-19 (n = 17). CONCLUSIONS: In line with scarce previous clinical and experimental findings, our results indicate that HFNC itself does not result in overall increased aerosol formation as compared to conventional oxygen therapy. This suggests there is no increased risk of respiratory pathogen transmission to health care workers during HFNC.